Body weight changes in child and adolescent athletes during a triathlon competition - Aragon-Vargas, L. F.; Wilk, B.; Timmons, B. W.; Bar-Or, O. (European Journal of Applied Physiology, 2013)
We examined young athletes during a triathlon performed in a hot climate. Complete or partial data were available for 95 athletes competing in the National Triathlon Championship in Costa Rica. Mean ± SD for age and body weight (BW) were 13.1 ± 2.5 years and 46.3 ± 11.5 kg, respectively. Race requirements included: 500 m swimming, 15 km cycling, 3.5 km running for juniors (9-13 years); 800 m swimming, 30 km cycling, 8 km running for seniors (14-17 years). WBGT on race day was >31 °C. BW recorded pre- and post-race was available for 92 athletes and performance data were available for 83 of these. Information regarding symptoms experienced during the race was available for 95 athletes. Change in BW (% Delta BW) was calculated and ranged from +0.6 to -2.4 % for junior boys (-1.2 ± 0.9 %), +0.7 to -2.5 % for junior girls (-1.3 ± 0.9 %), 0 to -2.8 % for senior girls (-1.3 ± 0.9 %), and +0.6 to -4.5 % for senior boys (-1.7 ± 1.1 %). Eighteen participants reported no medical symptoms. Of 77 participants who reported symptoms, 42.9 % reported exhaustion/fatigue, 36.4 % reported side stitch/cramp, and 23.4 % reported dizziness. Participants reporting no medical symptoms achieved almost identical (P = 0.99) % Delta BW as those reporting at least one symptom. %?BW was more negative (P = 0.005) in participants who reported dizziness (-1.9 % Delta BW) compared with those who did not (-1.4 % Delta BW). % Delta BW was associated with performance in junior girls (r = 0.47, P = 0.02) and senior boys (r = 0.51, P = 0.01), with a trend in junior boys (r = 0.41, P = 0.053) but not in senior girls (r = 0.004, P = 0.99). Young athletes participating in a triathlon in a hot climate can tolerate mild to moderate levels of dehydration, without detrimental effects to self-assessed health.